Revitalization of Greater Khartoum Urban Transportation System. Issue 1 (11th April 2018) - Bannaga, Sharaf Eldin Ibrahim
Khartoum metropolis depends on a single-modal transport – vehicular road system. Mass transport modes are completely absent making Khartoum unable to meet citizens' mobility demand. Thus passengers facing long time delays in transport stations. Slow traffic speeds and severe traffic jams result in long trip periods, high traffic accidents rates and high suspended particulate concentrations accumulating in the air. This situation is attributed to: Use of small-sized vehicles running on limited paved road network. Adoption of extensive grid iron planning patterns lacking multi-grade intersections. Eroded public transport fleet and extremely overcrowded urban centres. Negligence of public transport systems integration into landuse plans and urban structure restructuring difficulty crippled public transport revitalisation for no space is left for mass transport infrastructure construction. Moreover, transport systems' operation mismanagement and focus on economic development increased pressure on transport systems. This paper endeavours to point out the deficiencies in public transport services and proposes the areas of reformation. To revitalize urban transport, Khartoum main transport infrastructures must be efficiently operated by establishment of a talented transport authority supported by strong legislations and popular authorization and able to adopt sustainable mobility solutions to meet current and future traffic demands by: Rehabilitating and expanding the existing infrastructures. Deploying large-capacity multimodal transport systems including river transport, bus rapid transit systems, tramways and metropolitan railways to connect Khartoum polycentric and its sprawling outward growth. Mitigating environmental pollution and enforcing stringent road safety measures. Reviewing traffic laws to tighten traffic regulations and control traffic flows. Investment priority should be given to river transport. It is economically feasible, has large carrying capacity and safe and almost accident free. Furthermore, Nile Rivers dominate the metropolis, dictate urban configuration, direct urban growth, impose urban expansions patterns and influence spatial organization.